The quality of acid soils treated with seaweed (Kappapychus alvarezii) sap enriched biochar from Southeast Sulawesi, Indonesia - Laode Muhammad Harjoni Kilowasid; Dwita Siniona Manik; Nevianti Nevianti; Gusti Arya Komang; Puja Mutmainna; La Ode Afa; Tresjia Corina Rakian; Waode Siti Anima Hisein; La Ode Ahmad Nur Ramadhan; Syamsu Alam (Brawijaya University, 2023)
Biochar enriched with fertilizers has the potential to improve the quality of acid soils. In the agricultural sector, it was reported that the sap of Kappapychus alvarezii (K-sap) is often used as a biofertilizer. Therefore, this study aimed to (i) examine the character of biochar enriched with the K-sap and (ii) analyze the soil quality after incubation. This study was carried out using two treatment factors arranged in a randomized block design, namely the biochar dose at 0%, 2.5%, 5.0%, and 7.5% in weight and K-sap at concentrations of 0%, 5%, 10%, and 15%. Ten kilograms of acid soil were incubated with K-sap enriched biochar for up to 2 weeks in each experimental pot. The results showed that the absorption band increased with the K-sap concentration for the functional group associated with the OH-stretching of the biochar enriched with K-sap was stronger and wider than the unenriched. The peak elevation pattern detected by X-ray diffraction for all biochars was similar. The dosage of 7.5% biochar enriched with 5%-10% K-sap concentrations increased pH, EC, organic C, total N, C:N ratio, available P, and exchangeable K, Ca, Mg, and Si than those without treatment. Furthermore, ammonium and total spores of arbuscular mycorrhizal fungi decreased, flagellates increased with and without the biochar, while the nitrate, total bacteria, and fungi of all treatments were similar. Based on these results, it was concluded that biochar enriched with K-sap could improve the quality of acid soil.